1056 Perceived Financial Difficulty Predicts Sleep Quality In Participants With Type 2 Diabetes And Obstructive Sleep Apnea. (27th May 2020) - Morris, J L; Baniak, L; Belcher, S M; Imes, C; Luyster, F; Scott, P W; Sereika, S; Chasens, E R
Abstract: Introduction: People with multiple chronic conditions such as type 2 diabetes (T2D) and obstructive sleep apnea (OSA) are at increased risk for poor sleep quality. It is unclear if social determinants of health (SDoH) such as race, perceived financial difficulty, education, gender, and marital status are associated with sleep quality in this population. The purpose of this cross-sectional secondary analysis of data from the Diabetes Sleep Treatment Trial was to explore SDoH and disease severity as predictors of sleep quality in persons with both OSA and T2D. Methods: Disease severity was measured by Apnea-Hypopnea Index [(AHI) ≥ 5] and A1C for glycemic control. SDoH included perceived financial difficulty (none/moderate-severe), race (White/African American), sex (f/m), marital status (no/yes), education (≤ or > 2 years post high school), and age. Sleep quality was measured by Pittsburgh Sleep Quality Index (PSQI). Correlations and linear regression modeling investigated associations between SDoH and disease severity on sleep quality. Post-hoc correlations were explored for significant relations among SDoH. Results: The sample ( N = 229) was middle-aged (57.6 ± 10.0; 66 % White and 34% African American; and 54 % men vs. 46% women. Participants carried a high burden of disease (mean AHI = 20.7±18.1, mean A1C = 7.9 %±1.7%). Disease severity was not significantly associated with sleep quality (all p >.05). The perception of worse financial difficulty was the only SDoH that predicted worse sleep quality (b=-1.54, p =.015). Characteristics significantly associated with worse financial difficulty were being African American, female, ≤ 2 years post high school, and younger (all p <.01). Conclusion: Financial difficulty may be a more important predictor of subjective measures of sleep quality than disease severity in patients with OSA and T2D. Researchers and clinicians should be aware of these characteristics as potential markers of vulnerability to poor sleep quality in this population. Support: The National Institute of Diabetes and Digestive and Kidney Diseases (R01DK096028) and through the Clinical +Translational Research Institute grants UL1TR001857 and UL1TR000005.